audit PENGARUH TEKANAN ANGGARAN WAKTU,ETIKA AUDITOR DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT PADA KAP WILAYAH MEDAN: Tekanan Anggaran Waktu, Etika Auditor Dan Independensi - jenny zain jenny (Fakultas Ekonomi Prodi Akuntansi, 2021)
Abstract This study discusses the effect of time budget pressure, auditor ethics and auditor independence on audit quality. This research was conducted in 9 Public Accounting Firms in the Medan area. The sample technique used is simple random sampling. The data collection method in this study was conducted by survey or distributing questionnaires. The results of this study indicate that simultaneously time budget pressure, auditor ethics and independence have a significant effect on audit quality. Partially, time budget pressure has no effect on audit quality, auditor ethics has a positive effect on audit quality, and independence has a positive effect on audit quality.